Ages‐at‐death distribution of the early Pleistocene hominin fossil assemblage from Drimolen (South Africa). Issue 3 (5th January 2019) - Riga, Alessandro; Mori, Tommaso; Pickering, Travis Rayne; Moggi‐Cecchi, Jacopo; Menter, Colin G.
Abstract: Objectives: A prevailing hypothesis in paleoanthropology is that early Pleistocene hominin bones were accumulated in South African caves by carnivores, which used those shelters, and the trees surrounding them, as refuge and feeding sites. We tested this hypothesis at the site of Drimolen, by comparing its hominin age‐at‐death distribution to that of the nearby and roughly contemporaneous site of Swartkrans. Materials and methods: We employed standard dental aging systems in order to categorize the Drimolen hominin teeth into age classes of 5 years each. We then compared the age‐at‐death distribution for Drimolen with the published data available for the Swartkrans hominins. Results: Age‐at‐death distributions indicate that the age category "young adults" is the best represented age category at Swartkrans and the most poorly represented one at Drimolen. Moreover, Drimolen has a preponderance of infant specimens. Both sites have a low frequency of old adult specimens. Conclusions: Differences observed in frequencies of the age‐at‐death categories suggest different mechanisms of hominin skeletal accumulation at Drimolen and Swartkrans. Swartkrans' frequency curve reflects mortality in a population subjected to predation and is thus consistent with the carnivore‐accumulating hypothesis. In contrast, the Drimolen curve is similar to that of wild populations of living apes. Living primates have been observed exploiting caves as sleeping shelters, for nutritional, security, drinking, and thermoregulatory purposes. We suggest that similar cave use by Pleistocene hominins can explain, in large part, the accumulation of hominin bones at Drimolen. Such a conclusion is another illustration of the growing awareness that a "one‐size‐fits‐all" taphonomic model for South African early Pleistocene hominin sites is probably insufficient.